Effect of zinc treatment on growth and phytohormones accumulation in Triticum aestivum L. seedlings priming with abscisic acid - Kosakivska, I.V.; Voуtenko, L.V.; Vasjuk, V.A.; Shcherbatiuk, M.M. (Доповіді НАН України, 2019)
We investigated whether the priming with abscisic acid (ABA) alters the growth and the content of endogenous phytohormones
in winter wheat seedlings under zinc stress. It was shown that zinc at a concentration of 228 mg/l inhibits
the growth of the root system. Under these conditions, a decrease in the content of endogenous indole-3-acetic acid
(IAA), zeatin, and abscisic acid (ABA) and an increase in gibberellic acid (GA3), isopentenyladenosine (iPA) and
salicylic acid (SA) took place. After the adding of 10⁻⁶ M ABA to the incubation medium, the growth of seedling
roots, the level of stressful hormones ABA and SA became higher. The strategy of the adaptation of wheat seedlings
to zinc stress in the presence of exogenous ABA was aimed at the activation of root growth. Changes in the phytohormones
balance initiate protective mechanisms and a further adaptation of plants to a high concentration of zinc, and
the treatment of grains with exogenous ABA can be used to enhance the stress resistance. Досліджено вплив цинкового стресу на ріст та акумуляцію ендогенних фітогормонів у проростках озимої
пшениці, зернівки якої були праймовані абсцизовою кислотою (АБК). Показано, що в результаті інкубації
на розчині цинку надлишкової концентрації (228 мг/л) гальмувався ріст кореневої системи, знижувався
вміст ендогенної індоліл-3-оцтової, абсцизової кислот і зеатину та збільшувалась кількість гіберелінів,
ізопентеніладенозину та саліцилової кислоти. Після додавання в інкубаційне середовище 10⁻⁶ М АБК посилювався ріст коренів, вміст стресових гормонів абсцизової та саліцилової кислот зростав. Зміни у балансі фітогормонів ініціювали захисні механізми рослин до дії високої концентрації цинку, а отже, праймування зернівок екзогенною АБК може бути використане для підвищення стресостійкості. Исследовано влияние цинкового стресса на рост и аккумуляцию эндогенных фитогормонов проростками
озимой пшеницы, зерновки которой были праймированы абсцизовой кислотой (АБК). Показано, что при
инкубации на растворе цинка избыточной концентрации (228 мг/л) угнетался рост корней, уменьшалось
количество эндогенных индолил-3-уксусной, абсцизовой кислот, зеатина и увеличивалось содержание
гиббереллинов, изопентениладенозина и салициловой кислоты. После добавления в инкубационную
среду 10⁻⁶ М АБК рост корней усиливался, содержание стрессовых гормонов абсцизовой и салициловой
кислот возрастало. Изменения в балансе фитогормонов инициировали защитные механизмы растений к
действию высоких концентраций цинка, следовательно, праймирование зерновок экзогенной АБК может быть использовано для повышения стрессоустойчивости.